Life-stage and geographic location determine the microbial assemblage in Eurasian spruce bark beetle, Ips typographus L. (Coleoptera: Curculionidae) - Chakraborty, Amrita; Purohit, Arnab; Khara, Arunabha; Modlinger, Roman; Roy, Amit (Frontiers in Forests and Global Change, 2023)
Ips typographus L. (Coleoptera: Curculionidae) is one of the serious pests causing mass destruction of European spruce forests, with a substantial economic impact. Symbiotic microbes associated with bark beetles often play a definitive role in accomplishing their physiological and ecological functions by detoxifying chemicals, inhibiting pathogens, and offering nutrients. Although a few research works explored the microbes associated with I. typographus, much is yet to be studied to understand their adaptive ecology as holobionts comprehensively. The present study examined bacterial and fungal communities of larvae, adults, and feeding galleries from Austria and Czech Republic using high-throughput sequencing that elucidated the influence of geographic location, host, and life stage on the microbial assemblage in Eurasian spruce bark beetle, I. typographus. The most abundant bacterial genera in I. typographus included Pseudoxanthomonas, Spiroplasma, Pseudomonas, Cellulomonas, Tyzzerella, Bacillus, and Mycobacterium. Alternatively, Wickerhamomyces, Nakazawaea, Aspergillus, Ophiostoma, Cryptococcus, Rhexographium, Yamadazyma, Talaromyces, and Kuraishia were highly dominant fungal genera. Significant differences in bacterial and fungal community richness and diversity were detected among the tested samples. LEfSe analysis revealed species-specific bacterial and fungal biomarkers from different locations in the larvae, adults, and feeding gallery samples. PICRUSt2 and FUNGuild analysis documented putative roles of the bacterial and fungal communities in beetle holobiont and provided a foundation for downstream functional analyses. The current findings further enhanced our understanding of bark beetles as holobionts.